Effect of Spices on the Quality of Chinese Bacon - Peiling RAN; Yechuan HUANG; Chunlei PENG; Benbo XU; Keyuan ZHANG (Shipin gongye ke-ji, 2023)
In order to improve the quality of Chinese traditional smoked bacon, the 0.6%, 1.2% and 2.4% of spice extracts (including zanthoxylum bungeanum, star anise, bay leave, fennel, cinnamon and clove) were added in the processing of pickling. When being smoked, the corresponding proportion of spice residues after extract was added into the fumigation material. Following vacuum packing, the physicochemical, lipid and protein oxidation, nitrite residue, instrumental color, texture, microbial content, and sensory quality of the samples were respectively determined after 1 and 120 days of refrigeration. The results showed that the addition of 0.6% spice had little effect on bacon quality. The amount of addition amount increased to 1.2% and 2.4%, it could significantly inhibit lipid oxidation and microbial growth, and better maintained the soft texture and good elasticity of bacon during refrigeration. However, the addition of 2.4% had a little negative effect on instrumental color, sensory quality, and protein oxidation of products. Therefore, in the process of bacon processing, adding appropriate spices can improve the quality of bacon, and adding 1.2% spices has the best effect on improving the quality of bacon.